Strengths and weaknesses of food eco-labeling: a review - Tiboni-Oschilewski, Ornella; Abarca, Magdalena; Santa Rosa Pierre, Fabiana; Rosi, Alice; Biasini, Beatrice; Menozzi, Davide; Scazzina, Francesca (Frontiers in Nutrition, 2024)
Food labeling is increasingly expanding and adding more information to the food package. There is strong evidence about nutrition labeling effectiveness in driving food choice, especially if displayed in the front of package (FoP). Despite the growing attention to nutrition and sustainable diets, few countries have implemented sustainable labels or eco-labels that could address economic, social and/or environmental concerns. Implementing new techniques of eco-labeling emerges as a consumer-focused solution. However, evidence of the effectiveness of eco-labeling in driving consumers' choices is heterogeneous and not univocal. Thus, this review aims to summarize the evidence about the effectiveness of FoP eco-labeling in driving food choice and provide a reference framework of the eco-labeling initiatives relative to food package labeling. This narrative review addresses both the potential benefits as well as the main concerns that arise from the use of ecolabels. Although eco-labeling seems to provide a series of sustainability benefits for producers and consumers, the implementation of such policies should take into consideration potential trade-offs and inter-sectorial coordination to obtain bigger impacts, assuming that a policy itself cannot transform the whole food system. Eco-labeling could be encouraged and implemented within a set of policies shaping sustainable food systems.